De-noising method of pulse signal based on double-tree complex wavelet transform and morphological filtering - Dan LI; Huiqian WANG; Tong BAI; Jinzhao LIN; Yu PANG; Xiaoming JIANG; Yuhao JIANG (Dianxin kexue)
Common medical signals such as pulse signals, contain a variety of noises, have strong nonlinear and non-stationary. According to the previous wavelet transformation method, a pulse signals de-noising algorithm based on dual-tree complex wavelet transform（DTCWT）was proposed. With the advantage of simple construction, clear mathematical implications and low computational complexity, this method overcame the shift sensitive and the frequency aliasing in the discrete wavelet transform. The simulation results show that this algorithm can remove the power line interference and EMG interference, and the quantitative index of SNR and mean square error is superior to the traditional threshold de-noising algorithm. Therefore, the dual-tree complex wavelet transform de-noising algorithm will obtain clear medical wave signals.